Penerapan Instruksi pada Tahap Hypothesis Generation dalam Discovery Learning untuk Meningkatkan Kemampuan Menemukan dan Menghubungkan Konsep - As’ari, Faizal Nur; Widoretno, Sri; Nurmiyati, Nurmiyati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The research aims to increase the ability to find and connect concepts through implementation of instructions in hypothesis generation phase of discovery learning. This research is classroom action research that carried out for 2 cycles. Subjects are 28 students of high school students. The procedure of research consists: planning, observation, action, and reflection. Data were collected through observations, tests, documentation, and interviews. Validity of the data is performed using triangulation method. Data analysis using data reduction, data presentation, and inference with the qualitative descriptive analysis. The results showed the ability to find and connect a concept based on score of concept map in the pre cycle is range 2.84% - 5.41%. The average score of concept map in pre cycle is 3.46% with 12 students above average. The cycle I identified a score of concept map is range 5.8%-35.8%. The average score of concept map in the cycle I is 13.87% with 9 students above average. The cycle II identified a score of concept map is range 3.4% score-44.4%. The average score of concept map in cycle II is 18.3% with 16 students above the average, thus the ability to find and connect a concept based on range and an average score of concept map learners increased from pre cycle to cycle II, although the number of learners who is increasing is fluctuative.